Melatonin Levels in Patients With Primary Open-angle Glaucoma With High or Low Intraocular Pressure. Issue 2 (February 2019) - Kim, Jung Yong; Jeong, Ah Reum; Chin, Hee Seung; Kim, Na Rae
Abstract : Purpose: To evaluate circulatory melatonin levels by assessing nocturnal urinary excretion of 6-sulfatoxymelatonin (aMT6s) in patients with primary open-angle glaucoma (POAG) and to compare the high-tension group and the low-tension group. Methods: This study included 80 eyes of 41 POAG patients and 87 eyes of 44 control subjects. POAG group was further classified into high-tension group and low-tension group according to the pretreatment intraocular pressure (IOP). The first urine in the morning was collected and aMT6s were measured using a commercial ELISA kit. Urinary aMT6s levels were expressed as ng aMT6s/mg creatinine. Differences in melatonin levels among the control and POAG subgroups were evaluated by generalized estimating equation adjusting age, sex, sleep duration, and intereye correlation. Results: Urinary aMT6s/creatinine ratio did not differ between POAG and control group ( P =0.097). The difference in the aMT6s/creatinine ratio between the 3 groups—high-tension group with baseline IOP≥21 mm Hg (19.74±3.12 ng/mg), low-tension glaucoma group with baseline IOP<21 mm Hg (26.71±3.47 ng/mg), and control group (30.35±3.05 ng/mg)—was statistically significant ( P =0.046). Post hoc analysis revealed that the difference between the control and high-tension glaucoma groups was significant ( P =0.014), whereas the difference between the control and low-tension glaucoma groups was not ( P =0.436). Conclusions: This study found low melatonin levels in high-tension glaucoma compared with the control.